Cryptococcus gattii meningoencephalitis in a pediatric patient with cirrhosis. A case report - Ramírez, Jorge Luis; Mejía, Luis Fernando; Puchana-Quintero, María Esther; Rojas-Hernández, Juan Pablo (Universidad y Salud, 2019)
Introduction: In Colombia, Cryptococcosis is a rare invasive fungal infection. Objective: To report the clinical case of a child with Cryptococcus gattii meningoencephalitis whose risk factor was immune dysfunction associated with cirrhosis, a risk factor described in adults which in the reviewed literature has not been reported in children. Materials and methods: A non-systematic review of the literature and a summary of the most relevant aspects of the clinical history were performed. Results: We present the case of a 16-year-old male patient with a history of cirrhosis who came for consultation with a clinical presentation of 8 days of fever, persistent emesis, frontal headache, photophobia and tinnitus. The physical examination did not present neurological alterations. In the study of cerebrospinal fluid, he presented positive direct molecular tests for Cryptococcus neoformans/gattii and the culture reported growth of Cryptococcus gattii. Conclusion: In this case, the importance of suspecting opportunistic infections in patients who have immunodeficiencies not only secondary to HIV infections, but also to those caused by other factors that alter the immune response such as cirrhosis is highlighted.